Alcântara: memory and legacy of an industrial district in the process of cultural transformation of the city of Lisbon - Maddalluno, Rafaella (2019)
The best synthetic representation of the nature of the district of Alcântara today would be that of a tangled web. Indeed, its fundamental nature can be recognized in its fragmented fabric; it is through as a fragment, of the importance of finding meaning in the paratactic composition of language, bringing writing to a level zero where we are finally able to recognize the threads of hidden readings. The communication system network of the district presents a multiplicity of intertwinement. Just as fabric is intertwined, so are the streets, railways, public transport, bridges and rivers, giving life to structures such as the station, port, quays and docks. The river Tejo has assigned functions to the built-up landscape: industrial buildings and structures built to support production. In addition to the Tejo, buildings have also had to take into account the presence of a system of tributaries including the Alcântara canal. The arrival of the railway reinforced the existing centrality of communications, allowing the further development of industrial production. Finally, the construction of the 25 de Abril bridge brought about the ultimate polarity of the distinct and its urban image. It remains however a place of landing, a place of passage, a place of production, a place of residence and a place of a strongly marked identity.